1992
DOI: 10.1111/j.1439-0507.1992.tb00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent tinea pedis: a double blind study on the prophylactic use of fenticonazole powder*

Abstract: Summary. Tinea pedis is a common and frequently recurring dermatophytic infection, which is extremely difficult to eradicate. The often inevitable persistence of predisposing conditions, especially maceration, suggests that application of powders containing antifungal medication to the affected area could be effective in preventive therapy against recurrence. For this study we used one of the most recent azole antifungal agents, fenticonazole. Thirty patients affected with tinea pedis were cured with topical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Tinea pedis is extremely difficult to eradicate, as there are persistence conditions, mainly maceration, continuous use of topical antifungal medication is effective as a preventive therapy against recurrences 10 . Patel et al 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tinea pedis is extremely difficult to eradicate, as there are persistence conditions, mainly maceration, continuous use of topical antifungal medication is effective as a preventive therapy against recurrences 10 . Patel et al 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Tinea pedis is extremely difficult to eradicate, as there are persistence conditions, mainly maceration, continuous use of topical antifungal medication is effective as a preventive therapy against recurrences. 10 Patel et al 11 reported that topical treatment of tinea pedis with terbinafine and clotrimazole showed good efficacy of 75-80%, but the relapse rate in patients treated with terbinafine was 15% and among clotrimazole patients, it was 19%. Savin and Jorizzo 12 found that sertaconazole nitrate cream gave 70% mycological cure after 4 weeks of treatment, but 2 weeks after cessation of treatment only 47% remained mycological cure.…”
Section: Discussionmentioning
confidence: 99%
“…Необходимым условием для эффективного исполь зования данных препаратов в профилактике микозов стоп и онихомикозов является доказанная эффектив ность в терапии микозов стоп. Для этого за рубежом были проведены исследования, показавшие эффектив ность и безопасность разных порошков, содержащих азольные антимикотики, не выпускающихся в России [7,8,9]. С целью изучить эффективность новой формы 1% порошка клотримазола («кандид») нами было пред принято настоящее клиническое исследование.…”
Section: профилактическое использование противогрибковых средствunclassified
“…More recently, topical azoles such as fenticonazole powder have been used in adults with up to 100% cure rates. 138 Terbinafine 1% cream applied daily for 1 week also has been used effectively to treat T pedis, with >93% mycological cure rate at 4 weeks, and is approved for children 12 years and older. 139 Luliconazole was recently reported as a 1% cream trial for T pedis in adults, but less than 50% of the participants were cured on this regimen.…”
Section: Management Of T Pedis Outbreaksmentioning
confidence: 99%